Tingkat Kepatuhan dan Faktor yang Mempengaruhi Penggunaan Obat Antihipertensi pada Pasien Lansia di Posyandu Lansia Desa Drono - Aristhasari Putri; Avanilla Fany Septyasari; Belinda Apriliana (CERATA Jurnal Ilmu Farmasi, 2024)
The incidence of hypertension in the elderly has increased, which is caused by several factors that affect the level of compliance. This study was conducted to determine the level of compliance and factors that influence the use of antihypertensive drugs in patients at the elderly Posyandu Drono Village. This study used purposive sampling technique and questionnaire instrument of MARS-10, correlation analysis was performed with Chi-square test. The results showed that the level of patient compliance in the elderly Posyandu of Drono Village was not compliant (71.4%). Factors that have a correlation with compliance with the use of antihypertensive drugs are educational factors, with a value of p = 0,002 and family support factors with a value of p = 0,045. Providing comprehensive counseling about the desired outcomes, potential side effects, and proper medication usage can enhance patient knowledge, ultimately improving patient adherence. Moreover, family support can promote better adherence in elderly patients.